Effect of oxygen fugacity on the storage of water in wadsleyite and olivine in H and H–C fluids and implications for melting atop the transition zone - N. Bolfan-Casanova; L. Martinek; G. Manthilake; M. Verdier-Paoletti; P. Chauvigne (European Journal of Mineralogy, 2023)
This study aims to experimentally constrain the water storage capacities of olivine and wadsleyite at a depth near 410 km (12–14 GPa) under water-saturated conditions, as a function of temperature, oxygen fugacity, and the presence of carbon (molar H /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1b4178c77ca0d4bfee6c9ddd864f3a43"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-35-549-2023-ie00001.svg" width="8pt" height="14pt" src="ejm-35-549-2023-ie00001.png"/></svg:svg> C of 2). Experiments have been conducted in the multi-anvil press, with sealed double capsules to preserve fluids, at 1200 to 1400 ∘C and three different oxygen fugacities fixed at the rhenium–rhenium oxide buffer (RRO), nickel–nickel oxide buffer (NNO), and iron-wüstite (IW) for oxidizing, intermediate, and reducing conditions, respectively. The water contents of minerals were measured by Raman spectroscopy that allows a very small beam size to be used and were cross-checked on a few samples with NanoSIMS analyses.